Anomalous Behavior of Highly Active Helical Swimmers - Patil, Gouri; Ghosh, Ambarish (Frontiers in Physics, 2021)
Artificially designed self-propelled objects can allow studying active matter phenomena with great detail that is not possible in natural, e.g. biological systems. Here, we show experimental results on helical shaped, magnetically actuated, reciprocal swimmers, where the degree of randomness in the reciprocal sequence plays an important role in determining their effective motility. Here, for the first time we show the results at high activity levels where the degree of randomness is further affected by the presence of the surface, which in turn results in a non-monotonic increase of motility as a function of magnetic drive. It will be interesting to extend these studies to denser systems where the swimmers can interact with each other through hydrodynamic forces.